EXPERIENCE OF COMPLEX CONSULTING ON THE PROBLEM OF VITAMIN AND MINERAL CORRECTION IN CHILDREN AND ADOLESCENTS BY PEDIATRICIAN AT THE MEDICAL INSTITUTION AND PHARMACIST AT DRUGSTORE - S. V. Talashova; A. G. Khrykova; A. A. Trubnikov (Вопросы современной педиатрии, 2013)
Since the Federal Law № 323 «On the Basics of Russian Federation Population Health Protection» (2011) and the Order № 1175n «On Confirming the Procedure of Appointing and Prescribing Medicines» (2012) were administered, the legislative field of pediatricians' and pharmacists' activity has been changed. The present situation, especially at the initial stage of the mentioned laws realization, requires the necessity of patients' complex consulting as instead of the prescription with a definite medicine's name they will receive the one with the international nonproprietary name which might cause many questions. Modern complexes of vitamins and minerals have their own specific features as a medicinal group and a commodity. Based on the mentioned aspects, the article provides a practical example of complex consulting on the problem of vitamin and mineral correction in children and adolescents' nutrition and explains the necessity of vitamin and mineral complexes application, as well as details their administration peculiarities and the criteria of the quality of the products provided by the chemists.